A Perovskite Nanorod as Bifunctional Electrocatalyst for Overall Water Splitting. Issue 8 (20th December 2016) - Zhu, Yinlong; Zhou, Wei; Zhong, Yijun; Bu, Yunfei; Chen, Xiaoyang; Zhong, Qin; Liu, Meilin; Shao, Zongping
Abstract : The development of highly efficient and low‐cost electrocatalysts for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) is paramount for water splitting associated with the storage of clean and renewable energy. Here, this study reports its findings in the development of a nanostructured perovskite oxide as OER/HER bifunctional electrocatalyst for overall water splitting. Prepared by a facile electrospinning method, SrNb0.1 Co0.7 Fe0.2 O3–δ perovskite nanorods (SNCF‐NRs) display excellent OER and HER activity and stability in an alkaline solution, benefiting from the catalytic nature of perovskites and unique structural features. More importantly, the SNCF‐NR delivers a current density of 10 mA cm −2 at a cell voltage of merely ≈1.68 V while maintaining remarkable durability when used as both anodic and cathodic catalysts in an alkaline water electrolyzer. The performance of this bifunctional perovskite material is among the best ever reported for overall water splitting, offering a cost‐effective alternative to noble metal based electrocatalysts. Abstract : A novel SrNb0.1 Co0.7 Fe0.2 O3‐δ perovskite nanorod prepared by a facile electrospinning process exhibits excellent bifunctional electrocatalytic activity for oxygen evolution reaction and hydrogen evolution reaction in alkaline media, delivering an overall water splitting current density of 10 mA cm −2 at a cell voltage of merely ≈1.68 V while maintaining remarkable durability, which is among the best‐performing overall water splitting electrocatalysts reported so far.